The Effects of Taekwondo Training on Cardiorespiratory Fitness and Flexibility Among Adolescent Fitness Trainees - Fikadu, Desta; Eshetu (Ph.D), Abebe; Gemeda, Abebe (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2024)
Taekwondo is a dynamic unarmed combat style focused on self-defense, incorporating techniques such as punching, kicking, blocking, dodging, and parrying. This study aimed to explore the effects of taekwondo training on cardiorespiratory fitness and flexibility in adolescent fitness trainees. Using experimental research design, twenty-two male adolescents aged 10-18 years from Alex Fitness Training Center were randomly divided into two equal groups: the experimental group (EG, n = 11) and the control group (CG, n = 11). The EG underwent ten weeks of taekwondo training, participating in three sessions per week, each lasting 40 to 60 minutes. Their training included basic techniques, poomsae, sparring and self-defense. In contrast, the CG followed their regular fitness program. Both groups underwent pre- and post-testing, which assessed cardiorespiratory fitness via the Harvard step test and flexibility through static shoulder and wrist, trunk and neck tests, and the sit-and-reach test. The data were analyzed using SPSS version 25, employing descriptive statistics, paired t-tests, and independent t-tests at a significance level of p < 0.05. Cohen's d was used to evaluate effect sizes. Results indicated that taekwondo training significantly improved both cardiovascular fitness and flexibility (p < 0.05). The findings suggest a trivial effect size for cardiovascular fitness and a large effect size for flexibility. Consequently, taekwondo training is recommended for adolescents seeking to enhance their cardiorespiratory fitness and flexibility.